Exposure to landslides in rural areas in Central Italy. Issue 4 (28th July 2021) - Santangelo, Michele; Marchesini, Ivan; Bucci, Francesco; Cardinali, Mauro; Cavalli, Marco; Crema, Stefano; Marchi, Lorenzo; Alvioli, Massimiliano; Guzzetti, Fausto
ABSTRACT: Starting on 24th August 2016, Central Italy was struck by a six-month earthquake sequence that caused 303 victims and extensive major damages to urban areas and infrastructures, in some cases entire villages needed complete rebuilding. In this paper we present a map that portrays the overall susceptibility to multiple landslide types and the exposure to landslides of the rural-urban areas of the Castelsantangelo sul Nera Municipality, a typical village of the central Italian Apennine. The map is based on a procedure that ingests geomorphological data and models and groups the individual landslide susceptibility maps in a joint susceptibility and exposure map based on expert-defined criteria. The procedure has been applied to built-up and to undeveloped areas to highlight their exposure and was used as a tool for planning post-seismic reconstruction. We advise that such maps are used also as basic tool for ordinary urban planning.